A Narrative Inquiry between Input and Output Ability: CTS Connection in Debate for EFL: English - Yahya Al Abrar; Moh. Yamin; Elsa Rosalina (Journal of English Development, 2024)
This study delves into the correlation between critical thinking and input ability skills within the framework of debate. While debate often highlights spontaneous and responsive skills, the overlooked essential is the input ability, encompassing tasks like confirming information, summarizing, and catching details. These skills precede output ability and are crucial in effective debating. Drawing from sources spanning the past decade, this qualitative research employs the narrative inquiry method to explore the role of critical thinking in language input ability. Data collection involves questionnaires targeting students with debate experience, focusing on the impact of input and output skills on their debating. Utilizing interviews, the research reveals that a balance between input and output abilities is vital for successful debate performance. The result is participants have different points of view in choosing whether input or output which affects their critical thinking mostly, the strategies they used, the importance of output and input abilities, and emotional intelligence, it shows the need for strategies to enhance input abilities alongside output skills to gain maximum potential in debate. Future research aims to develop methods for fostering balanced improvement in input abilities, shifting from a sole focus on output proficiency.